2017
DOI: 10.1111/jph.12565
|View full text |Cite
|
Sign up to set email alerts
|

Resting Spore Dormancy and Infectivity Characteristics of the Potato Powdery Scab Pathogen Spongospora subterranea

Abstract: The soil‐borne potato pathogen Spongospora subterranea persists in soil as sporosori, which are aggregates of resting spores. Resting spores may germinate in the presence of plant or environmental stimuli, but direct evidence for resting spore dormancy is limited. A soilless tomato bait plant bioassay and microscopic examination were used to examine features of S. subterranea resting spore dormancy and infectivity. Dried sporosori inocula prepared from tuber lesions and root galls were infective after both sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…Soil inoculum was not eradicated by stimulant treatment over the trial periods considered in this study. It has recently been shown that not all resting spores of S. subterranea are responsive to germination stimulation, and that a level of constitutive dormancy exists (Balendres et al, 2017). Thus, regardless of efficiency of distribution within the soil, it would be expected that soil treatment with stimulants might not provide complete disease control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Soil inoculum was not eradicated by stimulant treatment over the trial periods considered in this study. It has recently been shown that not all resting spores of S. subterranea are responsive to germination stimulation, and that a level of constitutive dormancy exists (Balendres et al, 2017). Thus, regardless of efficiency of distribution within the soil, it would be expected that soil treatment with stimulants might not provide complete disease control.…”
Section: Discussionmentioning
confidence: 99%
“…The tomato bait test procedure of Balendres et al . (), modified from Merz (), was used to compare the effects of Hoagland's solution and distilled water on root infection. Three‐week‐old healthy tomato (cv.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…subterranea is a soil‐borne protozoan pathogen and is best known as the causal agent of powdery scab in potato tubers (Balendres, Tegg, & Wilson, ; Harrison, Searle, & Williams, ). The pathogen persists in the soil as dormant resting spores aggregated as clusters known as sporosori (Balendres, Tegg, & Wilson, ). Pathogenicity initiates with the germination of the resting spores stimulated by host plant root exudates resulting in the release of short‐lived primary zoospores into the soil (Balendres, Clark, Tegg, & Wilson, ; Balendres, Nichols, Tegg, & Wilson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Spongospora subterranea is known to persist in the soil for many years between potato crops as sporosori, which are aggregates of dormant resting spores (Kole, ; De Boer, ; Falloon, Merz, Lister, Wallace, & Hayes, ; Balendres, Tegg, & Wilson, ). This may be influenced by the presence of alternative host plants that maintain and build soil inoculum during the intercropping period (Falloon, ).…”
Section: Introductionmentioning
confidence: 99%